The 2016 update of the International Study Group (ISGPS) definition and grading of postoperative pancreatic fistula: 11 Years After - Bassi, Claudio; Hackert, Thilo; Büchler, Markus W. (Surgery, 2017)
Background: In 2005, the International Study Group of Pancreatic Fistula developed a definition and grading of postoperative pancreatic fistula that has been accepted universally. Eleven years later, because postoperative pancreatic fistula remains one of the most relevant and harmful complications of pancreatic operation, the International Study Group of Pancreatic Fistula classification has become the gold standard in defining postoperative pancreatic fistula in clinical practice. The aim of the present report is to verify the value of the International Study Group of Pancreatic Fistula definition and grading of postoperative pancreatic fistula and to update the International Study Group of Pancreatic Fistula classification in light of recent evidence that has emerged, as well as to address the lingering controversies about the original definition and grading of postoperative pancreatic fistula. Methods: The International Study Group of Pancreatic Fistula reconvened as the International Study Group in Pancreatic Surgery in order to perform a review of the recent literature and consequently to update and revise the grading system of postoperative pancreatic fistula. Results: Based on the literature since 2005 investigating the validity and clinical use of the original International Study Group of Pancreatic Fistula classification, a clinically relevant postoperative pancreatic fistula is now redefined as a drain output of any measurable volume of fluid with an amylase level >3 times the upper limit of institutional normal serum amylase activity, associated with a clinically relevant development/condition related directly to the postoperative pancreatic fistula. Consequently, the former “grade A postoperative pancreatic fistula” is now redefined and called a “biochemical leak,” because it has no clinical importance and is no longer referred to a true pancreatic fistula. Postoperative pancreatic fistula grades B and C are confirmed but defined more strictly. In particular, grade B requires a change in the postoperative management; drains are either left in place >3 weeks or repositioned through endoscopic or percutaneous procedures. Grade C postoperative pancreatic fistula refers to those postoperative pancreatic fistula that require reoperation or lead to single or multiple organ failure and/or mortality attributable to the pancreatic fistula. Conclusion: This new definition and grading system of postoperative pancreatic fistula should lead to a more universally consistent evaluation of operative outcomes after pancreatic operation and will allow for a better comparison of techniques used to mitigate the rate and clinical impact of a pancreatic fistula. Use of this updated classification will also allow for more precise comparisons of surgical quality between surgeons and units who perform pancreatic surgery.